Historical Analysis of Rural India: Contextualising Implications for Progress of Present Day Villages (Indian Journal of Extension Education, 2016)
India has 6,40,867 villages.The paper examines the typical transformations which Indian farming and rural community hadundergone right from the beginning of human civilization in Indian subcontinent, that is, the HarappanCivilization (3000 B.C) to the Post Liberalization Period which India is passing through since 1991. At a time when Government plans on development of Model Villages, the study highlights certain indicators of Model Village and the changes inthe major three sub indicators over the ages in history in the form of meta analysis leading to inferences. The historical inferences were supported adequately by secondary and primary data. Primary data was collected from four villages in Haryana (Green Revolution Belt) and West Bengal (Non Green Revolution Belt) for comparing socio economic status of villages of two regions. The inferences drawnwere found to provide the basis for setting target of future Indian agriculture forthe next 15 years.